A Numerical Investigation of the Deformation Mechanism of a Large Metro Station Foundation Pit under the Influence of Hydromechanical Processes. (12th March 2021) - Wang, Yan; Zhang, Yongjun; Li, Mingfei; Qi, Yi; Ma, Tianhui
Abstract : Considering the unique conditions of deep and large subway foundation pit excavation affected by heavy rainfall in soil-rock composite strata, this paper employs finite element numerical simulation methods to study foundation pit instability under the influence of heavy rainfall. According to the hydraulic coupling conditions caused by rainfall, a fluid-solid coupling numerical model for a deep and large subway foundation pit in soil-rock composite strata is established in this paper. By selecting the Anshan road station of Qingdao subway line 4 as the engineering background, various parameters related to foundation pit excavation affected by heavy rainfall at different excavation depths were analyzed. The study found that after the foundation pit was excavated, the surrounding pore water pressure decreased and the pore water pressure near the ground surface increased rapidly due to rainfall. As the horizontal distance from the foundation pit increased, the pore water pressure at the same depth also increased. The excavation of the foundation pit caused uplift of the bottom of the pit. After rainfall, the uplift value decreased compared with that before rainfall. With increasing excavation depth, the decreased value of the bottom uplift decreased and then increased. The rainfall caused the horizontal displacement of the pit walls on both sides of the pit to increase. When the excavation depth was 10 m, the horizontal displacements on both sides of the pit were equivalent. When the excavation depth was 20 m, the horizontal displacement was concentrated in the first 10 m; when the excavation depths were 30 m and 40 m, the horizontal displacement was concentrated in the first 13 m. This finding shows that when the foundation pit was affected by rainfall, the sidewall collapsed at a distance of 13 meters from the ground. As the excavation depth increased, the depth of excavation instability was closer to the bottom of the pit. The research in this paper can provide a reference for the construction of deep and large foundation pits in similar composite ground conditions that are affected by rainfall.